Controlled Digital Lending of Library Books in Canada - De Castell, Christina; Dickison, Joshua; Mau, Trish; Swartz, Mark; Tiessen, Robert; Wakaruk, Amanda; Winter, Christina (Partnership, 2022)
This paper explores legal considerations for how libraries in Canada can lend digital copies of books. It is an adaptation of A Whitepaper on Controlled Digital Lending of Library Books by David R. Hansen and Kyle K. Courtney, and draws heavily on this source in its content, with the permission of the authors. Our paper considers the legal and policy rationales for the process—“controlled digital lending”—in Canada, as well as a variety of risk factors and practical considerations that can guide libraries seeking to implement such lending, with the intention of helping Canadian libraries to explore controlled digital lending in our own Canadian legal and policy context. Our goal is to help libraries and their lawyers become better informed about controlled digital lending as an approach, offer the basis of the legal rationale for its use in Canada, and suggest situations in which this rationale might be strongest.